2008
DOI: 10.1590/s0102-86502008000100007
|View full text |Cite
|
Sign up to set email alerts
|

Preventing intraperitoneal adhesions with vitamin E and sodium hyaluronate/carboxymethylcellulose: a comparative study in rats

Abstract: Purpose:To compare the effectiveness of intraperitoneally administered vitamin E with the sodium hyaluronate/ carboxymethylcellulose membrane (HA/CBMC) in preventing postoperative intraperitoneal adhesion formation. Methods: Sixty Wistar rats underwent a laparotomy and adhesions were induced (IA). The animals were divided into four groups: group 1, control (IA); group 2 (IA + Vitamin E): group 3 (IA+HA/CBMC) and group 4 (IA+ Vitamin E + HA/CBMC). The Vitamin E (groups 2 and 4) and HA/CBMC (groups 3 and 4) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 23 publications
0
25
0
7
Order By: Relevance
“…Increases cGMP leading to reduced collagen synthesis and increases in fibroblast apoptosis [276,277] Some efficacy in rat models (oral delivery) [278,279] Increased colonic bursting pressure and angiogenesis in rat model in the presence of infection [279] Methylene blue Inhibits NO synthase; reduces free radical oxygen but mechanism in preventing adhesions unknown [280] Some efficacy in rat models [280][281][282] May induce adhesions at high doses [280] Impairs anastomotic healing [282] Catalase Reduces oxidative stress Some efficacy in rat model [283] Vitamin E Antioxidant Efficacy comparable to Seprafilm in rat model [284] Opioids (opium, morphine) Unknown mechanism; postulated that opium receptor decreases inflammation [285] Some efficacy in rat model (reduced length, thickness, and severity) [285] (Continued ) WARD AND PANITCH: ABDOMINAL ADHESIONS: PATHOGENESIS AND SOLUTIONS May reduce oxidative stress [286] Some efficacy in rat bacterial peritonitis model [286] Mixture of lidocaine and prilocaine more effective than lidocaine alone [286] Honey Unknown mechanism; may reduce oxidative stress [287] Some efficacy in rat model (oral delivery [288] and peritoneal delivery [287]) Improved histology and anastomotic busting pressure in rats [288] Sphingosine kinase 1 delivered by adenovirus Enhances mesothelial cell migration accelerating wound healing [289] Some efficacy in rat model [289] neurokinin-1 receptor antagonist (aprepitant, CJ-12-255]…”
Section: Efficacy Comparable To Seprafilm In Rat Model [51] Role Of Amentioning
confidence: 99%
“…Increases cGMP leading to reduced collagen synthesis and increases in fibroblast apoptosis [276,277] Some efficacy in rat models (oral delivery) [278,279] Increased colonic bursting pressure and angiogenesis in rat model in the presence of infection [279] Methylene blue Inhibits NO synthase; reduces free radical oxygen but mechanism in preventing adhesions unknown [280] Some efficacy in rat models [280][281][282] May induce adhesions at high doses [280] Impairs anastomotic healing [282] Catalase Reduces oxidative stress Some efficacy in rat model [283] Vitamin E Antioxidant Efficacy comparable to Seprafilm in rat model [284] Opioids (opium, morphine) Unknown mechanism; postulated that opium receptor decreases inflammation [285] Some efficacy in rat model (reduced length, thickness, and severity) [285] (Continued ) WARD AND PANITCH: ABDOMINAL ADHESIONS: PATHOGENESIS AND SOLUTIONS May reduce oxidative stress [286] Some efficacy in rat bacterial peritonitis model [286] Mixture of lidocaine and prilocaine more effective than lidocaine alone [286] Honey Unknown mechanism; may reduce oxidative stress [287] Some efficacy in rat model (oral delivery [288] and peritoneal delivery [287]) Improved histology and anastomotic busting pressure in rats [288] Sphingosine kinase 1 delivered by adenovirus Enhances mesothelial cell migration accelerating wound healing [289] Some efficacy in rat model [289] neurokinin-1 receptor antagonist (aprepitant, CJ-12-255]…”
Section: Efficacy Comparable To Seprafilm In Rat Model [51] Role Of Amentioning
confidence: 99%
“…Prevention is a far more desirable goal (Gomel et al, 1996;Mettler, 2003;Scott-Coombes et al, 1993), and much effort has been expended on adhesion prevention using various chemical compounds and barriers (Corrales et al, 2008;Guo et al, 2009;Ilbay et al, 2004;Kutlay et al, 2004;Mettler et al, 2003;Oncel et al, 2004). Systematic reviews of these treatments have reported that none consistently prevent adhesion formation (Kumar et al, 2009;Metwally et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E presents interesting biological properties and activities for preventing intraperitoneal adhesions. In vitro studies have reported that it has antioxidant, anti-inflammatory, anticoagulant and antifibroblastic effects, and playing a role in diminishing the production of collagen [3][4][5] . In recent studies, it has been suggested that intraperitoneal application of MB can be used as an effective agent in the prevention of postoperative adhesions 6 .…”
Section: Introductionmentioning
confidence: 99%